PERENCANAAN SISTEM PEMBUMIAN GRID-ROD PADA GARDU INDUK 150 KV NEW SANUR - Rian Sanjaya, Dewa Made; Indra Partha, Cok Gede; Dyana Arjana, I Gede (Jurnal SPEKTRUM; Vol 7 No 1 (2020): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2020.v07.i01.p10, 2020)
At the substation there are several electrical equipment including power transformers, power breakers, phase change devices, and protective equipment, to keep all equipment in the substation a grounding system is needed. To obtain a good earth system in the planning of the substation must pay attention to the type of soil. In this study there are several methods of earthing system analyzed, including: plate earthing system, mesh earthing system and grid-rod earthing system. This analysis aims to obtain a good earthing system design with a low earth resistance value. From the results of analysis and calculation of the earth grounding system, the earth resistance value is obtained using 34 plates of 0.3555 Ohm. The Earth Mesh system obtained the value of the ground resistance of 0.3447 Ohm with a distance of D is 10 meters then for the planning of the ground-up systems construction of the New Sanur subsite that will be used as a reference is a grid-rod ground system, with The length of the grid is 100 meters, and the width of the grid is 60 meters, then the optimization design obtained from the results of analysis and calculation is 0,3324 useing the distance between the conductor of the grid is 10 meters and the number of rod is 32 Rod.